The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1097/jnr.0000000000000317
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effectiveness of Interventions on Increasing Participation in Cervical Cancer Screening

Abstract: Background:Although cervical cancer is highly preventable through regular screenings using Pap smear or human papillomavirus–deoxyribonucleic acid tests, cervical cancer remains a prevalent women's health issue across the world. Therefore, encouraging women to screen for cervical cancer is very important for the early detection of cervical cancer.Purpose:The purposes of this study were to (1) assess the effectiveness of three interventions that are typically used to increase the uptake of cervical cancer scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 27 publications
2
24
0
16
Order By: Relevance
“…Training Centres (KETEMs) provide screening service free of charge, these rates are expected to be substantively higher. However, the low rate of having a Pap smear test found in this study is in parallel with the results of previous national reports (6,14). However, in several previous reports, it has been stated because of having no health insurance or a low socio-economic status, women could not join the screening programs (22) and medical costs have been reported to be barrier to not having the Pap smear test (23).…”
Section: Considering That Cancer Early Diagnosis Screening Andsupporting
confidence: 89%
See 2 more Smart Citations
“…Training Centres (KETEMs) provide screening service free of charge, these rates are expected to be substantively higher. However, the low rate of having a Pap smear test found in this study is in parallel with the results of previous national reports (6,14). However, in several previous reports, it has been stated because of having no health insurance or a low socio-economic status, women could not join the screening programs (22) and medical costs have been reported to be barrier to not having the Pap smear test (23).…”
Section: Considering That Cancer Early Diagnosis Screening Andsupporting
confidence: 89%
“…In another study, 79% of the women in an age range of 40-64 years were found to have had a Pap smear test one in the previous 3 years (21). In Turkey, in three different studies conducted in different groups from different regions, these ratios were reported to be 13.5%, 25.2%, and 66.1%, respectively (6,7,14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bu sonuçlar kadınların sık görülen kanserler ve erken tanısıyla ilgili bilgilendirilmesinin farkındalıklarını arttırarak, erken tanı yöntemlerine başvurma oranlarını arttıracağını göstermektedir (25). Günümüzde serviks kanseri nedeni ile olan ölümlerin %90'ı tarama çalışmalarının sistematik ve yaygın şekilde yapılmadığı gelişmekte olan ülkelerde görülmektedir (11) kadınlara serviks kanseri ve pap smear testi ile ilgili eğitim/broşür verilmesiyle ve evde izlemiyle serviks kanseri bilgi düzeylerinde ve taramalara katılımlarında anlamlı artışlar görülmüştür (26,27). Sağlık çalışanlarının pap smear testi ile ilgili farkındalık yaratma ve pap smear taramalarına katılım oranlarını arttırmada önemli sorumlulukları bulunmaktadır.…”
Section: Rahim Ağzı Kanseri Ve Pap Smear Testi Sağlık İnanç Modeli öLçeğiunclassified
“…As access to DDAs increases, patients' knowledge about hepatitis C could influence uptake of hepatitis screening, linkage to treatment, and treatment outcomes, thereby impacting the likelihood of successful elimination campaigns. Participant's disease-related knowledge has been associated with increased participation in screening campaigns for many diseases, including cervical cancer [7], hepatitis B [8], and HIV [9]. Among patients enrolled in hepatitis C treatment programs, higher patient knowledge has been associated with reduced loss to follow-up [10], while other educational interventions, such as singlesession group educational interventions and multisession one-on-one educational interventions, have been associated with increased willingness to initiate treatment, reduced time to treatment initiation, increased adherence, and increased likelihood of sustained virologic response (SVR) [11][12][13].…”
mentioning
confidence: 99%